Impact Strategy (PDEODE) In The Acquisition Of Grammatical Concepts In The Fifth Grade Literary Students And The Development Of Critical Thinking - Salih Hussein, Falah; Salih Fayyadh, Maad (Opción, 2019)
The researchers followed the experimental design, which consists of two groups, one experimental and the other control and intentionally selected two schools in which to apply the experiment, the researchers used a simple random method, the total number of the two divisions (62) students to be an experimental group studying using the strategy (PDEODE) has been careful before The initiation of the experiment to statistically equal the two research groups in a number of variables believed to affect the safety of the experiment. The researchers identified the educational material to be taught, the Ar- abic grammar book and the researchers prepared model teaching plans for both groups. The research tool was a test of the acquisition of grammatical concepts, which included (33) test items of a multiple-choice type measuring the three processes to acquire the concept. Of (30) paragraphs were calcu- lated honesty and consistency for this test. After the initialization of the two research tools, the Critical Thinking Test was applied. After the completion of the experiment, the researchers applied the Research Tools (Post-Concept Grammar Test and Post-Critical Thinking Test) to the two research groups. 1 - There is a statistically significant difference at the level (0.05) between the average scores of the experimental group studying the grammar as per strategy (PDEODE) and in the test of the acquisition of the concept of grammar and for the benefit of the experimental group. In the test of critical thinking after and for the experimental group and in the test before and after critical thinking and in favor of the test after. In light of the research results, the researchers recommended a number of recommendations, including: The need to conduct training courses for teachers and to inform them on how to formulate questions, and include levels of concept acquisition and equip them with teaching methods of thinking types, especially critical thinking. Among the suggestions put forward by the researchers the effectiveness of the strategy (PDEODE) in the achievement of fifth grade literary students in the subject of Arabic grammar and the development of their visual thinking